Объяснение:
1. 5(2×0,6+1)-3=5(1,2+1)-3=5×2,2-3=11-3=8
2.а) 5х^3×(-2х^2)=-10х^5
б) 2а-(6в-а)+(6в-2а) = 2а-6в+а+6в-2а=а
в)(3x - 1)(3x + 1) + - (3x + 1)^2 = 9x^2 + 1 - 9x^2 + 6x + 1 = 6x + 2
г)(2х^3у)^3=8х^9у^3
3. а)2ху-6у^2=2у(х-3у)
б) а^5-4а^3=а^3(а^2-4)
в) а^3-2а^2+18-9а=а^2(а-2)+9(2-а)
4. а) 4(2-4х)=3-6х
8-16х=3-6х
-16х+6х=3-8
-10х=-5
х=-5÷(-10)=0,5
б) (х-1)(х+7)=0
х^2+7х-х-7=0
х^2 +6х-7=0
за теоремой Виета
х1+х2=-6
х1×х2= -7. х1=-7. х2=1
в) 2у^2-18=0
2у^2=18
у^2=9
у=3;у=-3
5. 1 день -х
2 день - х-10
3 день - х-10-5
х+х-10+х-10-5= 50
3х -25=50
3х=75
х= 25
1день 25км
2 день 15км
3день 10км
15*(X+3)*(X-5) + 10*(X+2)*(X-5) +6*(X+2)*(X+3) \ 30*(X+2)*(X+3)*(X-5) = 2
15*(X^2-2X-15) +10*(X^2-3X-10) +6*(X^2+5X+6) = 60*(X+2)*(X+3)*(X-5)
15X^2 - 30X - 225 + 10X^2 - 30X - 100 +6X^2 +30X + 36 =
= 31X^2 - 30X - 289
60*(X+2)*(X+3)*(X-5) = 60*(X^2+5X+6)*(X-5) = 60*(X^3 - 19X -30) = 60X^3 - 1140X - 1800
31X^2 - 30X - 289 = 60X^3 - 1140X - 1800
60X^3 - 31X^2 - 1110X - 1511 = 0
Берём производную:
180X^2 - 62X - 1110X = 0
2*(90X^2 - 31X - 555) = 0
D = 961 - 4*90*(-555) = 961 + 199800=200761 V D = 448
X1 = 31 + 448 \ 180 = 2.6
X2 = 31 - 448 \ 180 = - 417\180 = - 2.3